THE SOCIO-PSYCHOLOGICAL FEATURES OF SELF-CONSCIOUSNESS FORMED AT ADOLESCENTS WITH ADDICTIVE BEHAVIOUR LIVING IN CONFLICTING FAMILIES - Prib, Glib (PSYCHOLOGICAL JOURNAL, 2019)
The article examines the social and psychological peculiarities of self-consciousness formed at adolescents with addictive behaviour living in conflicting families. The components of self-consciousness and self-esteem, adolescents’ tendency to deviant behaviour, aggressive and hostile reactions, and their behavioural patterns in conflicts are investigated. Adolescence is the age of appearance of self-awareness, so adolescents want that their uniqueness can be recognized by other people, but, at the same time, they are psychologically dependant on peers. Therefore, adolescents effectively use their ego-position. A special form of adolescents’ self-awareness is their sense of maturity, which can be defined as a new concept in their consciousness, through which adolescents compare themselves with others, finds patterns for assimilation, builds their relationships with people and realigns theirs activities. The article reveals that the problem of harmful substance use by adolescents living in conflicting families is researched insufficiently in Ukraine. According to the results of our research, specific features of self-consciousness, manifested in the deformation of self-esteem, are developed at adolescence. Addictive behaviour can be developed because conflict interactions of adolescents with their family environment, namely, because negative family impact on their personal development. In turn, incertitude, tension, hostility and aggressiveness, characteristic for adolescents, are prerequisites for destructive addictive behaviour. In general, the examined adolescents showed the following psychological characteristics: inability to overcome difficulties, ignoring obstacles, apathetic submission to a group with antisocial moods, decreased self-criticism, anxious expectation. Adolescents experienced strangeness and alienation, lack of communications and emotional instability under stress, which provoked addictive behaviour. In conflicting families, adolescent addictive behaviour means their desire to change the mental states or not to focus their attention on a conflict. Addiction for adolescents is a universal way to get rid of conflicts in their families. Deviant adolescents have high self-esteem and do not feel guilty, unlike normative adolescents who are characterized by low self-esteem and guilt. Adolescents with deviant behaviours tend to paint in bright colours their personal traits, but can follow moral norms and standards and make a good impression. The need for further research on the various aspects of conflicting families, which adolescents use psychoactive substances, is noted.